(untitled) (World Bulletin of Public Health, 2023)
The evaluation of the diagnostic value of cystatin C in patients with hypertension (HP) in combination with obesity was carried out and the values of the calculated glomerular filtration rate (GFR) were compared based on the concentration of creatinine and cystatin C. 2 groups of patients were examined: group 1 – 32 patients diagnosed with HP 1 risk of category 2 with obesity, aged 20 – 44 years old (mean age 32 ± 1.3 years) with a well–established proteinsynthetic liver function; group 2 - 33 practically healthy patients (comparison group), reliably comparable in gender and age. It was revealed that the level of cystatin C in the group of patients with HP and obesity was significantly higher (1.77 ± 0.14 mg/l) compared with the comparison group (0.74 ± 0.02 mg/l). GFR in patients with HP in combination with obesity, based on the determination of creatinine levels was 127.3 ± 4.2 ml/min. and it was significantly higher than the GFR value in this category of patients, calculated by the level of cystatin With 50.3 ± 4.2 ml/min /1.73 m2 , since the calculation of GFR by creatinine is influenced by the body weight of patients, and it was excessive. It is advisable to calculate GFR in obese patients with HP by the level of cystatin C, since it more accurately determines the presence of renal dysfunction in patients.